Manajemen Mutu Pembelajaran PAI dalam Upaya Mewujudkan Generasi Berakhlakul Karimah di SMK Negeri 3 Purworejo - Zaenatun Sururiyah (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
This research is based on the importance of akhlakul karimah. In connection with this, this study aims to determine the Management of PAI Learning in Realizing the Generation of Akhlakul Karimah at SMK N 3 Purworejo. This research is a qualitative research. Data collection used interviews, observation, and documentation, and the validity of the data used triangulation, and data analysis techniques included data reduction, data presentation, and drawing conclusions. The results of this study indicate that: (1) PAI learning planning in realizing a generation of good morals at SMK N 3 Purworejo is carried out before the beginning of the year's learning begins. In terms of making teaching tools, teachers make preparations by making annual programs, semester programs, syllabus and lesson plans according to the material and directions of the school principal. (2) PAI subject teachers at SMK N 3 Purworejo have carried out the learning process in accordance with what had been previously prepared. Implementation of learning is carried out in accordance with the educational calendar, a predetermined schedule, and in accordance with the Learning Implementation Plan (RPP) that has been made. (3) Teachers who teach PAI carry out an assessment of the success of learning PAI in realizing a generation of good morals at SMK N 3 Purworejo in several ways, including by having written exams/tests (daily and end-of-semester assessments) and assessing students' attitudes/morals in daily life. The standards used as a measuring tool for assessing the success of students in learning PAI learning are changes in the attitude of students and their practice in behaving, speaking, behaving, and changes in the attitude of students towards teachers in everyday life. (4) Each PAI teacher carries out follow-up learning by reporting learning outcomes in each subject taught to the school principal. Reporting of learning outcomes is carried out every semester. Learning outcomes in the form of assessments will be recapitulated and reported both orally and in writing. Learning outcomes are also conveyed by homeroom teachers directly to parents/guardians of students when taking the study results report book.